2014
DOI: 10.1128/aac.02781-14
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Interferon Gamma-Induced Reactive Oxygen Species with Ceftazidime Leads to Synergistic Killing of Intracellular Burkholderia pseudomallei

Abstract: Burkholderia pseudomallei, a facultative intracellular pathogen, causes severe infections and is inherently refractory to many antibiotics. Previous studies from our group have shown that interferon gamma (IFN-␥) interacts synergistically with the antibiotic ceftazidime to kill bacteria in infected macrophages. The present study aimed to identify the underlying mechanism of that interaction. We first showed that blocking reactive oxygen species (ROS) pathways reversed IFN-␥-and ceftazidime-mediated killing, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…IL‐18 was originally discovered as an IFN-γ-inducer which induces IFN-γ production from Th1 and NK cells with or without IL-12 upon stimulation with antigens 47 , 48 . IFN-γ is an important inflammatory factor which induced inflammatory response and ROS can cause cell death through apoptosis and necroptosis 49 , 50 . We tested the expression of potential synergistic mediators of IL-18 signaling, such as IL-15 and IL-12, in irradiated BM.…”
Section: Discussionmentioning
confidence: 99%
“…IL‐18 was originally discovered as an IFN-γ-inducer which induces IFN-γ production from Th1 and NK cells with or without IL-12 upon stimulation with antigens 47 , 48 . IFN-γ is an important inflammatory factor which induced inflammatory response and ROS can cause cell death through apoptosis and necroptosis 49 , 50 . We tested the expression of potential synergistic mediators of IL-18 signaling, such as IL-15 and IL-12, in irradiated BM.…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that two cellular antioxidants and ROS pathway inhibitors, N-acetylcysteine (NAC) and glutathione (GSH), abolished the synergistic effect of IFN-γ and ceftazidime to reduce intracellular bacterial burden in B. thailandensis infected macrophages [24]. These results supported the role of IFN-γ-induced ROS in contributing to the reduction of bacteria in the combination treatment of macrophages.…”
Section: Semet Treatment Of Infected Macrophages Leads To Significantmentioning
confidence: 62%
“…We had previously seen evidence of a dynamic interplay between the extracellular and intracellular spaces of our macrophage infection model [24], whereby extracellular bacteria could gain entrance to the inside compartments of macrophages, and intracellular bacteria, upon rupture or lysis of the macrophage, could exit back into the extracellular space. Such movement of bacteria between intracellular and extracellular spaces would be predicted based on the known pathogenesis of Burkholderia [4,8].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations